O uso de nomes gerais no âmbito político - Paola Santos Lima Soares (2020)
This research aims to analyze patterns of the use of general nouns in the discourse of leftwinged and right-winged parties in Brazil, in the light of the Theory of Variation and Change proposed by William Labov (2008[1972]) and of notions about stylistic variation, when referring to groups of people in the political sphere. More specifically, at times, users choose to refer to specific categories of individuals, and some other times they choose to abstract distinctions by electing vague forms such as general nouns that, according to Halliday and Hasan (1995 [1976]), Amaral (2013a, 2013b, 2017) and Amaral e Ramos (2014), are forms with minimum descriptive content. This study starts from the assumption of Bourdieu (2008) that the use of generic forms in reference to people is related to conservatism and that of Rickford (2001) and Irvine (2001) that stylistic variation can be conditioned by ideological positions. The general objective is to verify if there is stratification of the use of general nouns among speeches of parties of opposite polarization, regarding the ideological spectrum, in three distinct synchronies: 2011, 2015 and 2019. The hypothesis is that the introduction of conservative discourses in the Brazilian political scenario, a phenomenon observed since 2015 (CHALOUB; PERLATTO, 2015), has caused changes in the pattern of the use of general nouns, making them more frequent in contexts of generic interpretation in right-wing speeches. Another hypothesis that we want to test is that, according to Bourdieu (2008), conservative discourses use more euphemistic ways to deal with groups of individuals, such as “humble people” and “simple people”. In this sense, another objective of this work is to make a semantic analysis of the expressions that are formed from the association between general and adjectival names and adjective locutions, to verify if there is a predominance of forms that express subjective evaluation, preferably euphemistic, in speeches of right. As a result of these purposes, the speeches of federal deputies of the most representative party on the left and the most representative party on the right were analyzed, and 1481 occurrences with general nouns were found. Regarding the first objective, the results confirm the hypothesis that there was a gradual increase in general nouns in contexts of generic interpretation in right-wing discourses. In 2011, these elements represented 20.4%; in 2015, they accounted for 27% of the data, and in 2019, they reached 33.4%. On the other hand, the pattern of use of general nouns in these contexts, on the opposite side of the ideological spectrum, remained with non-significant variations: 21.5%, in 2011; 22.7%, in 2015, and 20.4%, in 2019. In relation to the second objective of this study, it was found that, in rightwing speeches, expressions that express subjective evaluation in the three synchronies are more present, but that the use of euphemistic forms is greater in 2011, becoming infrequent in 2015. In 2019, they are replaced by the expressions “pessoas de bem” (good people), which maintain the appeal to order, without, however, target the less favored classes.